Alternative kynurenic acid synthesis routes studied in the rat cerebellum - Blanco Ayala, Tonali; Lugo Huitrón, Rafael; Carmona Aparicio, Liliana; Ramírez Ortega, Daniela; González Esquivel, Dinora; Pedraza Chaverrí, José; Pérez de la Cruz, Gonzalo; Ríos, Camilo; Schwarcz, Robert; Pérez de la Cruz, Verónica (Frontiers in Cellular Neuroscience, 2015)
Kynurenic acid (KYNA), an astrocyte-derived, endogenous antagonist of α7 nicotinic acetylcholine and excitatory amino acid receptors, regulates glutamatergic, GABAergic, cholinergic and dopaminergic neurotransmission in several regions of the rodent brain. Synthesis of KYNA in the brain and elsewhere is generally attributed to the enzymatic conversion of L-kynurenine (L-KYN) by kynurenine aminotransferases (KATs). However, alternative routes, including KYNA formation from D-kynurenine (D-KYN) by D-amino acid oxidase (DAAO) and the direct transformation of kynurenine to KYNA by reactive oxygen species (ROS), have been demonstrated in the rat brain. Using the rat cerebellum, a region of low KAT activity and high DAAO activity, the present experiments were designed to examine KYNA production from L-KYN or D-KYN by KAT and DAAO, respectively, and to investigate the effect of ROS on KYNA synthesis. In chemical combinatorial systems, both L-KYN and D-KYN interacted directly with peroxynitrite (ONOO-) and hydroxyl radicals (OH•), resulting in the formation of KYNA. In tissue homogenates, the non-specific KAT inhibitor aminooxyacetic acid (AOAA; 1 mM) reduced KYNA production from L-KYN and D-KYN by 85.1 ± 1.7% and 27.1 ± 4.5%, respectively. Addition of DAAO inhibitors (benzoic acid, kojic acid or 3-methylpyrazole-5-carboxylic acid; 5 µM each) attenuated KYNA formation from L-KYN and D-KYN by ~35% and ~66%, respectively. ONOO- (25 µM) potentiated KYNA production from both L-KYN and D-KYN, and these effects were reduced by DAAO inhibition. AOAA attenuated KYNA production from L-KYN + ONOO- but not from D-KYN + ONOO-. In vivo, extracellular KYNA levels increased rapidly after perfusion of ONOO- and, more prominently, after subsequent perfusion with L-KYN or D-KYN (100 µM). Taken together, these results suggest that different mechanisms are involved in KYNA production in the rat cerebellum, and that, specifically, DAAO and ROS can function as alternative routes for KYNA produc